2013
DOI: 10.1371/journal.pcbi.1002909
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the High-Affinity Zinc Binding Site Validates a Refined Human Dopamine Transporter Homology Model

Abstract: The high-resolution crystal structure of the leucine transporter (LeuT) is frequently used as a template for homology models of the dopamine transporter (DAT). Although similar in structure, DAT differs considerably from LeuT in a number of ways: (i) when compared to LeuT, DAT has very long intracellular amino and carboxyl termini; (ii) LeuT and DAT share a rather low overall sequence identity (22%) and (iii) the extracellular loop 2 (EL2) of DAT is substantially longer than that of LeuT. Extracellular zinc bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 95 publications
(154 reference statements)
4
91
0
Order By: Relevance
“…We previously described procedures to generate free outward-facing homology models for DAT inserted into a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine membrane, which were optimized and tested for stability in 200 ns molecular dynamics simulations (Stockner et al, 2013. At the end of the simulations, the three best-scored models were selected for docking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously described procedures to generate free outward-facing homology models for DAT inserted into a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine membrane, which were optimized and tested for stability in 200 ns molecular dynamics simulations (Stockner et al, 2013. At the end of the simulations, the three best-scored models were selected for docking.…”
Section: Resultsmentioning
confidence: 99%
“…The protein models were created following the procedure published earlier (Stockner et al, 2013. The models were based on the outward-facing structures of the leucine transporter, LeuT Aa , crystallized from Aquifex aeolicus (Protein Data Bank identity 3F3A) (Singh et al, 2007) because the models created from the occluded conformation resulted in a potentially too narrow S1-binding site.…”
Section: Pharmacoinformaticsmentioning
confidence: 99%
“…They have offered an essential molecular context for the investigation of the mechanism of uphill neurotransmitter reuptake transport enabled by the coupling with the transmembrane Na + gradient 1,10 . Our current understanding of functional mechanisms in NSS has been further shaped by the large body of structure-function studies of LeuT and other related bacterial transporters, carried out both experimentally 11-17 and computationally [11][12][13][14]16,[18][19][20][21][22][23] , and more recently by findings from molecular dynamics (MD) simulations of DAT [24][25][26][27][28][29] and SERT 30,31 constructs. Together, these studies have suggested for the transport cycle in NSS proteins an allosteric process that is consistent with the alternating access mechanism 32 in which concerted dynamic rearrangements on the extracellular (EC) and intracellular (IC) sides of the transporter result from ion-and ligand-specific conformational rearrangements.…”
mentioning
confidence: 99%
“…Interestingly, our results are in harmony with earlier observations on the inhibition of the dopamine transporter DAT by Zn 2ϩ (29,30). The target of the divalent cation is an endogenous zinc binding site formed by four amino acid residues, two from EL2 and two from EL4 (31). Because the inhibition by zinc is not due to the formation of a covalent bound, it is impossible to monitor inhibition following preincubation under conditions favoring outward-or inward-facing conformations.…”
Section: Discussionmentioning
confidence: 99%